New energy vehicle electric skylight control device - LIANG HAIQUAN; SHEN YANWEN; MO XUEMIN; WANG LIYAN (2017)
The invention relates to the technical field of new energy vehicles, and discloses a new energy vehicle electric skylight control device. The new energy vehicle electric skylight control device comprises a micro-processor, a hall sensor, a current sensor, a relay, a direct-current motor, skylight glass, a photovoltaic assembly, a solar battery, a vehicle power supply, a voltage converter and the like. An A/D port of the micro-processor is correspondingly connected with the hall sensor and the current sensor. An I/O port of the micro-processor is correspondingly connected with a skylight switch, an ignition signal and the relay. The relay is connected with the direct-current motor, and outputs a control signal to control start and stop of the direct-current motor. The solar battery is connected with the vehicle power supply. The vehicle power supply is connected with the relay, and is connected with the micro-processor through the voltage converter to supply power for the relay and the micro-processor. By adop